Multifunctional specificity of the protein C/activated protein C Gla domain. - PRESTON, ROGER (American Society for Biochemistry and Molecular Biology, 2006)
Activated protein C (APC) has potent anticoagulant and anti-inflammatory properties that are mediated in part by its interactions with its cofactor protein S and the endothelial cell protein C receptor (EPCR). The protein C/APC Gla domain is implicated in both interactions. We sought to identify how the protein C Gla domain enables specific protein-protein interactions in addition to its conserved role in phospholipid binding. The human prothrombin Gla domain, which cannot bind EPCR or support protein S cofactor activity, has 22/45 residues that are not shared with the human protein C Gla domain. We hypothesized that the unique protein C/APC Gla domain residues were responsible for mediating the specific interactions. To assess this, we generated 13 recombinant protein C/APC variants incorporating the prothrombin residue substitutions. Despite anticoagulant activity similar to wild-type APC in the absence of protein S, APC variants APC(PT33-39) (N33S/V34S/D35T/D36A/L38D/A39V) and APC(PT36/38/39) (D36A/L38D/A39V) were not stimulated by protein S, whereas APC(PT35/36) (D35T/D36A) exhibited reduced protein S sensitivity. Moreover, PC(PT8/10) (L8V/H10K) displayed negligible EPCR affinity, despite normal binding to anionic phospholipid vesicles and factor Va proteolysis in the presence and absence of protein S. A single residue variant, PC(PT8), also failed to bind EPCR. Factor VIIa, which also possesses Leu-8, bound soluble EPCR with similar affinity to wild-type protein C, collectively confirming Leu-8 as the critical residue for EPCR recognition. These results reveal the specific Gla domain residues responsible for mediating protein C/APC molecular recognition with both its cofactor and receptor and further illustrate the multifunctional potential of Gla domains.
PUBLISHED
Keywords: Clinical medicine; Hematology; Gla domains